The Role of Skin-to-Skin Contact and Breastfeeding on Atonic Postpartum Hemorrhage - Wedad M. Almutairi; Susan M. Ludington; Mary T. Quinn Griffin; Christopher J. Burant; Ahlam E. Al-Zahrani; Fatmah H. Alshareef; Hanan A. Badr (MDPI AG, 2020)
Objectives: were to (a) determine incidence of postpartum hemorrhage (PPH) in all women delivering between 2009 and 2015, and (b) determine the amount of Estimated Blood Loss (EBL) and duration of the third stage of labor in each subgroup for women with or without PPH, and (c) compare EBL and duration of 3rd stage of labor between subgroups in groups of women with or without PPH. Design: A retrospective chart review conducted using codes for atonic PPH. Setting: Records from a University based tertiary setting, 264 charts were reviewed and data from 154 charts were analyzed. One-way ANOVAs followed with post-hocs and a 2-way ANOVA were conducted. Results: PPH rate increased by 47.50% from 2009-2015. For women with PPH, EBL was lower in skin to skin contact (SSC) + Breastfeeding (BF) subgroup. For women without PPH, EBL was lower in SSC only subgroup. Third stage of labor duration was longer in women with PPH. Conclusions: Study confirmed the increasing trends of PPH due to uterine atony and proposed role of SSC and BF in decreasing EBL and shorten the duration of the 3rd stage of labor for PPH women, usefulness of SSC and BF as physiologic practices merit further study.